Smart Grid та організація інформаційного обміну в електроенергетичних системах - Кириленко, О.В.; Блінов, І.В.; Танкевич, С.Є. (Технічна електродинаміка, 2012)
The features of the Smart Grid implementation in the design of automated control systems and control systems which are associated with the electricity market operation are described. The international regulatory framework is analyzed and the basic information architectures, which have found an application in the development of such systems are defined. Series of international standards, ensuring the implementation of Smart Grid technologies for creating automated control systems and structures inherent in the electricity market are identified.